FKBP5 polymorphism is associated with insulin resistance in children and adolescents with obesity. (January 2018) - Fichna, Marta; Krzyśko-Pieczka, Izabela; Żurawek, Magdalena; Skowrońska, Bogda; Januszkiewicz-Lewandowska, Danuta; Fichna, Piotr
Summary: Objective: Since metabolic syndrome shares several clinical features with hypercortisolism, it was hypothesised that genes altering individual glucocorticoid (GC) sensitivity might be implicated in pathogenesis of obesity and its adverse outcomes. FKBP5 gene encodes a chaperon protein in the GC receptor (GR) complex, which modulates steroid action upon target genes. Its functional variant, rs1360780, may enhance FKBP5 gene transcription, affect GR signalling and thereby influence the hypothalamo–pituitary–adrenal axis. We investigated the association of rs1360780 with obesity and metabolic characteristics in 250 obese children and adolescents (mean age 12.3 ± 3.6 years, BMI ≥95th percentile). Methods: Anthropometric measurements, body composition, biochemical and hormonal results were analysed. Genotyping of rs1360780 was compared with 568 lean controls. Results: Impaired fasting glucose was present in 8.8%, glucose intolerance in 10.4%, diabetes in 2.8% and dyslipidemia in 28.8% obese individuals. Hypertension was diagnosed in 34 out of 143 patients. No difference was found in FKBP5 polymorphism distribution between subjects with obesity and controls ( p  > 0.05). Stratification by rs1360780 revealed no differences in body mass and composition. However, carriers of the minor allele displayed enhanced insulin resistance ( p  = 0.009) and elevated serum triglyceride ( p  = 0.006), whereas cholesterol, HbA1c, and oral glucose challenge results were similar for all genotypes. Morning ACTH and cortisol did not differ but evening cortisol was higher in minor allele carriers ( p  = 0.039), although this association was lost in logistic regression analysis. Conclusion: This study does not support the association of FKBP5 with obesity but demonstrates plausible implication of its variant in susceptibility to obesity-related insulin resistance and hypertriglyceridemia.